The Effect of Question-Answer Relationship on the Reading Comprehension Score of the First Graders of SMK - Lilla Roosantie (Widya Mandala Surabaya Catholic University, 2014)
The purpose of this study is to investigate the effect of applying Question Answer Relationship (QAR) in reading comprehension achievement This study is quasi experimental study with non-random assignment. Two groups (experimental and control) taken from two classes of Computer -Networking specialization were involved each group consists of 32 students. To control the internal threat the researcher put into consideration to sample selection, instrument and pre-testing. The data was collected based on the data collection procedure: selection the sample, preparing lesson plan, preparing instrument administering the pre-test, carrying out treatment, and administering the pot-test. The researcher compared and tested the mean score at the .05 level of significance determine whether the effect of the treatment was significant. The result of this research leads to a conclusion that the students taught using QAR achieved better scores in reading comprehension. In other words, QAR improves the students reading comprehension.